Climate preservation in urban communities case studies - Clark, Woodrow W. (Butterworth-Heinemann, an imprint of Elsevier, 2019)
Climate Preservation in Urban Communities Case Studies delivers a firsthand, applied perspective on the challenges and solutions of creating urban communities that are adaptable and resilient to climate change. The book presents valuable insights into the real-life challenges and solutions of designing, planning and constructing urban sustainable communities, providing real world examples of innovative technologies that contribute to the creation of sustainable, healthy and livable cities. Examples of successes, failures and solutions are presented based on a cross disciplinary approach for infrastructural systems, including discussions of drinking water, wastewater, power systems, broadband, Wi-Fi, transportation and green buildings technologies.